The Academic Climate and Organizational Support Influence on Performance of Lecturers Scientific Publications (Study at the Private University Accredited in West Java) - Komala Putri, Ratna; Tisnawati Sule, Ernie; Effendi, Nury; ., Hilmiana (International Journal of Engineering and Technology, 2018)
Objective - This article aims to produce a study of: Academic climate, organizational support and the performance of scientific publications of lecturers. Then examine the influence of academic climate and organizational support on the performance of lecturer scientific publications. Research on the performance of scientific publications is still very rare, let alone linking the issue to the academic climate and organizational support. So that research on this scientific publication should be done immediately so that scientific publications of lecturers in Indonesia can increase, especially the performance of scientific publications of lecturers at the private university in West Java.Method - The research design used in this research is mixed method Research (MMR). The analytical tool uses a Partial Lease Square.Findings - Scientific publications of lecturers will increase both in quantity and quality if conducive academic climate and organizational support activities. Academic climate and organizational support affect the performance of lecturer scientific publications, either partially or simultaneously. Simultaneously influence the academic climate and organizational support to Performance of Scientific Publication of Lecturers, amounted to 54,4%. While partially Academic climate and Organizational Support influential significantly to Performance of Scientific Publication of Lecturers, which is Academic climate has a greater influence (34,8%).Â Â